2019
DOI: 10.3390/cancers11091350
|View full text |Cite
|
Sign up to set email alerts
|

Human Ovarian Cancer Tissue Exhibits Increase of Mitochondrial Biogenesis and Cristae Remodeling

Abstract: Ovarian cancer (OC) is the most lethal gynecologic cancer characterized by an elevated apoptosis resistance that, potentially, leads to chemo-resistance in the recurrent disease. Mitochondrial oxidative phosphorylation was found altered in OC, and mitochondria were proposed as a target for therapy. Molecular evidence suggests that the deregulation of mitochondrial biogenesis, morphology, dynamics, and apoptosis is involved in carcinogenesis. However, these mitochondrial processes remain to be investigated in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 47 publications
6
50
1
Order By: Relevance
“…Mainly expressed in plasma cells, IRF4 was reported to be associated with tumor stage, histological grade, and completeness of chemotherapy 44 . Multiple evidence has shown that TEAD1 and TFAM are oncogenes in OC, which is concordant with our results 45 , 46 . The role of ZNF124 in OC is little known, but it was found to inhibit apoptotic death and function as an oncogene in hematopoietic cells 47 .…”
Section: Discussionsupporting
confidence: 94%
“…Mainly expressed in plasma cells, IRF4 was reported to be associated with tumor stage, histological grade, and completeness of chemotherapy 44 . Multiple evidence has shown that TEAD1 and TFAM are oncogenes in OC, which is concordant with our results 45 , 46 . The role of ZNF124 in OC is little known, but it was found to inhibit apoptotic death and function as an oncogene in hematopoietic cells 47 .…”
Section: Discussionsupporting
confidence: 94%
“…Mainly expressed in plasma cells, IRF4 was reported to be associated with tumor stage, histological grade, and completeness of chemotherapy [55]. Multiply evidence has shown that TEAD1 and TFAM are oncogenes in OC, which is concordant with our results [56,57]. The role of ZNF124 in OC is little known, but it was found to inhibit apoptotic death and function as an oncogene in hematopoietic cells [58].…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggested that overexpression of Sirt3 can induce OC cell death. In terms of mitochondrial dynamics, a previous study revealed that stabilization of Sirt3 can increase mitochondrial biogenesis and cristae remodeling in OC tissues (38). Additionally, stabilization of optic atrophy protein 1, which increased resistance to apoptosis, was demonstrated to be regulated by increasing the expression of Sirt3 and prohibitin 2 (38).…”
Section: Sirt3 In Ocmentioning
confidence: 98%
“…In terms of mitochondrial dynamics, a previous study revealed that stabilization of Sirt3 can increase mitochondrial biogenesis and cristae remodeling in OC tissues (38). Additionally, stabilization of optic atrophy protein 1, which increased resistance to apoptosis, was demonstrated to be regulated by increasing the expression of Sirt3 and prohibitin 2 (38). Activation of Sirt3 has also been found to enhance the sensitivity of OC cells to cisplatin (39), rendering Sirt3 to be a novel therapeutic target.…”
Section: Sirt3 In Ocmentioning
confidence: 99%